Disparate Effects of Diabetes and Hyperlipidemia on Experimental Kidney Disease - Watson, Anna M. D.; Gould, Eleanor A. M.; Moody, Sarah C.; Sivakumaran, Priyadharshini; Sourris, Karly C.; Chow, Bryna S. M.; Koïtka-Weber, Audrey; Allen, Terri J.; Jandeleit-Dahm, Karin A. M.; Cooper, Mark E.; Calkin, Anna C. (Frontiers in Physiology, 2020)
It is well established that diabetes is the major cause of chronic kidney disease worldwide. Both hyperglycaemia, and more recently, advanced glycation endproducts, have been shown to play critical roles in the development of kidney disease. Moreover, the renin-angiotensin system along with growth factors and cytokines have also been shown to contribute to the onset and progression of diabetic kidney disease; however, the role of lipids in this context is poorly characterised. The current study aimed to compare the effect of 20 weeks of streptozotocin-induced diabetes or western diet feeding on kidney disease in 2 different mouse strains, C57BL/6 mice and hyperlipidaemic apolipoprotein (apo) E knockout (KO) mice. Mice were fed a chow diet (control), a western diet (21% fat, 0.15% cholesterol) or were induced with streptozotocin-diabetes (55mg/kg/day for 5 days) then fed a chow diet and followed for 20 weeks. The induction of diabetes was associated with a 3-fold elevation in glycated haemoglobin and an increase in kidney to body weight ratio regardless of strain (p<0.0001). ApoE deficiency significantly increased plasma cholesterol and triglyceride levels and feeding of a western diet exacerbated these effects. Despite this, urinary albumin excretion (UAE) was elevated in diabetic mice to a similar extent in both strains (p<0.0001) but no effect was seen with a western diet in either strain. Diabetes was also associated with extracellular matrix accumulation in both strains, and western diet feeding to a lesser extent in apoE KO mice. Consistent with this, an increase in renal mRNA expression of the fibrotic markers, fibronectin, was observed in diabetic C57BL/6 mice (p<0.0001). In summary, these studies demonstrate disparate effects of diabetes and hyperlipidaemia on renal injury, with features of the diabetic milieu other than lipids suggested to play a more prominent role in driving renal pathology.